TEACHERS’ USE OF INFORMAL FORMATIVE ASSESSMENT IN SENIOR SECONDARY SCHOOL CHEMISTRY CLASSROOMS IN SWAZILAND - Masuku, Mzenzi S.; Oloyede, O I.; Kelly, Victoria L. (International Journal of Research -GRANTHAALAYAH, 2019)
The social-economic role of education as a major driver of human development calls for quality education that is rooted on effective teaching and learning. While Swaziland aspires to have products of her secondary education system efficiently joining tertiary training or the workplace, the SGCSE performance trend in Physical Science currently features below expectation. This study explored how teachers in Swaziland used informal formative assessment in their senior secondary school Chemistry lessons. Three purposively sampled lessons from Form 4 and Form 5 were observed. Data were collected through field notes and analysed using inductive content analysis. Findings showed that teachers used informal formative assessment by explaining misunderstood content in fresh ways, giving learners remedial work, initiating hand-clapping, repeating or adjusting initial and probing questions. All in all, teachers used informal formative assessment in line with standard practices though they often resorted to telling learners answers to seemingly demanding questions.